Spatio-temporal dynamics of suspended particulate matter in the middle Niger River using in-situ and satellite radiometric measurements - Boubacar Moussa, Moussa; Abdourhamane Touré, Amadou; Kergoat, Laurent; Lartiges, Bruno; Rochelle-Newall, Emma; Robert, Elodie; Gosset, Marielle; Alkali Tanimoun, Bachir; Grippa, Manuela (Journal of hydrology. Regional studies, 2022)
Study Region: Middle Niger River Basin (MNRB), Ansongo to Niamey, Sahel, West Africa. Study Focus: Although MNRB hydrology and the red flood phenomena have been addressed in the past literature, water quality parameters and suspended particulate matter (SPM) dynamics remain poorly known. SPM impacts dam silting, exacerbating flooding, and microbial water quality. This study couples in-situ SPM measurements to radiometric measurements by in-situ and satellite sensors to analyse the temporal and spatial evolution of SPM in the MNRB and assess the contribution of the local flood (red flood) to SPM in Niamey. New Hydrological Insights for the Region: SPM is composed of very fine kaolinites with a major mode around 200–300 nanometers which results in high reflectance in the visible and infrared bands. Radiometric measurements by both radiometer and Sentinel-2 MSI sensors are well correlated to in-situ SPM, allowing efficient spatio-temporal monitoring of SPM concentration. SPM increases very rapidly at the beginning of the rainy season, reaching a peak, characterized by very high SPM values, about one month before the red flood. Satellite data highlight the significant contribution of the right bank tributaries to SPM in the MNRB during this period. SPM then decreases and remains low despite the second runoff increase (black flood) arriving in Niamey after the end of the rainy season from the upper basin. [Display omitted] •Analysis of 3 hydrological cycles of SPM dynamics in the Middle Niger River.•Accurate monitoring of SPM dynamics by in situ and remote radiometric sensors.•High SPM from right bank tributaries during red flood, low SPM during black flood.•Very fine kaolinite particles, mode at 200 nm, cause high water leaving radiance.